Characteristics and long-term outcome of right ventricular involvement in Takotsubo cardiomyopathy - Becher, Tobias; El-Battrawy, Ibrahim; Baumann, Stefan; Fastner, Christian; Behnes, Michael; Loßnitzer, Dirk; Elmas, Elif; Hoffmann, Ursula; Papavassiliu, Theano; Kuschyk, Jürgen; Dösch, Christina; Röger, Susanne; et al. (International journal of cardiology, 2016)
Objective - Takotsubo cardiomyopathy, also known as stress-induced cardiomyopathy (SCM) resembles a reversible cardiomyopathy that is characterized by localized wall motion abnormalities in the absence of stenotic coronary vascular disease. Patients typically present with apical ballooning of the left ventricle (LV), however the right ventricle (RV) is also affected in up to 50.0% of patients. Long-term prognosis of classical SCM resembles that of patients after ST elevation myocardial infarction. Data on long-term prognosis of biventricular compared to classical SCM is controversial. The aim of this study was therefore to analyze patients with biventricular SCM regarding in-hospital outcome and long-term prognosis. - Materials and methods - 114 consecutive patients with SCM were retrospectively analyzed. 88 patients presented with classical SCM, 26 patients (22.8%) were diagnosed with biventricular SCM. Follow-up was conducted for a total of 4.4years. Mean age was 67.1years with 83.3% of patients being female. The primary endpoint was a composite of all-cause mortality, recurrence of SCM and re-hospitalization due to heart failure. - Results - Although patients with biventricular SCM presented with a tendency towards an increased rate of cardiogenic shock (30.8% vs. 15.9%; p=0.09) and significantly more usage of inotropic support upon hospital admission (34.6% vs. 13.6%; p=0.01), there was no difference concerning the primary endpoint in both groups (50.0% vs. 44.3%; p=0.31). Furthermore, there was no difference in mortality both in-hospital (7.7% vs. 7.9%; p=0.66) and during long-term follow-up (27.3% vs. 23.1%; p=0.46). - Conclusion - Patients with biventricular SCM have the same in-hospital and long-term outcome compared to classical SCM.
Gesehen am 27.06.2019
Available online 28 June 2016